In vivo effect of bromelain from Ananas comosus on Staphylococcus aureus skin infection in an animal model - Siti Nur Atikah Zul; Mohd Shazwan Shazdee Wahab; Elysha Nur Ismail; Reezal Ishak (Universitas Nahdlatul Ulama Surabaya, 2025)
The skin is the largest organ in the body and aids in protection against foreign microorganisms. Any physical changes to the skin structure would eventually promote microbial colonization that leads to soft tissue and skin infections. This study was conducted to establish the effectiveness of bromelain extraction from Ananas comosus in treating Staphylococcus aureus skin infections in BALB/c mice. A total of 18 male mice aged 9 - 12 weeks were divided into three groups: bromelain-treated, iodine-treated, and negative control groups. The skin infection was inflicted on the dorsal area of the mouse by first removing the hair and applying the tape-stripping method before inoculating it with S. aureus. The microbial samples from the infected skins of the mice were collected on days 1, 4, and 7 after infection using a Q-Swab apparatus and streaked on blood agar. The samples were incubated at 37°C for 24 h and the S. aureus colony formation unit (CFU) from each group was calculated. The results indicated that mice treated with bromelain had a lower average number of S. aureus CFU (2.55x10-2 CFU/mL) compared with iodine-treated mice (1.56x10-2 CFU/mL) and had a significantly different count compared with the negative control group (8.24x10-2 CFU/ml) on day 7 post-infection. Data were analyzed using one-way ANOVA and Student’s t-test for significant differences with p<0.05. In conclusion, the findings of this study showed that bromelain can be developed and applied as an antimicrobial agent against S. aureus skin infection.